Gender Differences in Circumstances Surrounding First Injection Experience of Rural Injection Drug Users in the United States - Young, April M. (2013)
BACKGROUND: Research has demonstrated that there can be substantial gender differences in circumstances surrounding initiation of injection drug use; however, little is known about the gendered dynamics of first injection in rural areas where syringe exchange is inaccessible or among those who predominantly inject prescription medications. The present study examines gender differences in first injection experience among rural residents who predominantly inject prescription opioids. METHODS: Interview-administered questionnaires collected data from a sample of injection drug users (n=394) recruited from Appalachian Kentucky using respondent-driven sampling. RESULTS: Women were more likely to have initiated injection due to social-pressure (p=0.001), received the drugs as a gift (p=0.011), initiated in their partner’s home (p=0.004) and in their partner’s presence (p<0.001), been injected by their partner (p<0.001), used an unclean syringe (p=0.026), and received the syringe from their partner (p<0.001). Women were also more likely to report having engaged in sexual intercourse before or after initiation (p<0.001). Men were more likely to have personally purchased the drugs (p=0.002), to have acquired the syringe from a pharmacy/clinic (p=0.004), and to have injected with a friend (p=0.001) or family member (p=0.020). Men were also more likely to have a friend administer the first injection (p=0.007). CONCLUSIONS: In this population of rural drug users, notable gender differences in injection initiation were observed. Social pressure played a more substantial role in women’s first injection experience, and male partners had an integral role in women’s initiation.